Ordinances of the Corporation of the District of Southwark and the Acts of Assembly Relating Thereto, at 49, Firing of Guns, § 1 (1829) - (:unkn) unknown (General Publisher, 1750)
That if any person shall fire any gun or other fire-arm, or shall make, or cause to be made, or sell or utter, or offer to expose to sale, any squibs, rockets or other fire-works, or shall cast, throw or fire any squibs, rockets or other fire-works, within any of the said towns or boroughs, without the Governor’s special license for the same, every such person or persons, so offending, shall be subject to the like penalties and forfeitures, and to be recovered in like manner, as in and by an act, passed in the eighth year of the reign of King George the first, entitled, “ An Act for Preventing Accidents, Etc
--
Keywords: DISCHARGE